Domitianè - Kaiè Latomia (Umm Balad) : Le praesidium et les carrières - Brun, Jean-Pierre; Botte, Emmanuel, 1955-; Cardon, Dominique 1965-; Cuvigny, Hélène 1956-; Bulow-Jacobsen, Adam; Cavassa, Laetitia 1943-; Sachet, Isabelle 1976- (Fouilles de l'Institut français d'archéologie orientale du Caire ;, 2024)
The excavations carried out at Domitianè/Kainè Latomia (Umm Balad) in 2001‑2003 by the French Ministry of Foreign Affairs/IFAO have added to our knowledge of the occupation of the Eastern Desert of Egypt in Roman times. This site, located in the Porphyrites massif, has a rock deposit of "granito verde fiorito di bigio" (gray flowered green granite). The attempt to exploit it led to the construction of a small fort by the army under Domitian. It served as a base for the quarry workers. The gate inscription, although very mutilated, indicates a date of construction around 88–92. This early phase does not seem to go beyond the beginning of Trajan’s reign. The praesidium was probably abandoned thereafter, until around 146, when it was reoccupied for only a short period of time, before being abandoned again.The examination of the two quarries provides a lot of information about the organization of the work, but what can be established about their respective histories remains speculative for the most part. The use of Kainè Latomia finally ended in failure, probably due to the poor quality of the stone. However, some blocks were sent to Rome where they were used first of all for the decoration of the Domus Flavia (Flavian Palace) on the Palatine. 4e de couverture .